(untitled) (Journal Of Educational and Psychological Researches, 2022)
The current study aims to identify:The meta-motivation and Uniqueness seeking of the study sample. The correlated relationship among them. The present study sample consists of (400) students from the colleges of engineering, University of Baghdad, and the University of Technology in the academic year (2019-2020), and the researcher has adopted the Chen Scale (1995)to measure the meta-motivation after its translation into Arabic by(Al-Samawi,2011).The scale includes six dimensions. The researcher has also adopted the Snyder&Fromkin scale (1980) to measure the uniqueness seeking after translating and adapting it into the Arabic environment. The scale consists of three dimensions. The results show that students of the Faculties of Engineering have high meta-motivation levels, while they a moderate rate of uniqueness seeking . Furthermore, there is a significant and predictive correlated relationship among the meta-motivation and uniqueness seeking